O trabalho do professor TEA na educação básica: contribuições para a educação especial e inclusiva no município de Parintins/AM - Maia, Tâmily Bentes (Brasil, 2025)
This article addresses the role of support teachers for students with Autism Spectrum Disorder (ASD) in regular education, focusing on the municipality of Parintins. The aim is to understand the work of these professionals by contextualizing the special and inclusive education policies, presenting relevant legislation, and identifying the challenges faced in the inclusion of students with ASD. The research, based on a qualitative approach, uses bibliographic and documentary analysis, as well as an online questionnaire. The participants were an ASD teacher, a school manager. The results highlight the importance of ongoing professional development, teacher mediation, and adapted pedagogical strategies, as well as challenges such as resource scarcity and the adaptation of students to the school environment